GENERALIZATION OF CLASSIFICATION SIGNS REFLECTING VARIOUS ASPECTS OF DIFFERENTIATION OF REGIONS - E. Berezina; L. Vasileva (Вестник университета)
The classification features, that reflect various aspects of inter-regional differentiation, have been summarized. The initial information for the analysis were the works of domestic and foreign scientists. The methodological basis of the study was a set of formal logical methods. The obtained results confirm, that the researchers do not stop searching for new features, serving as the basis for future classifications. In some cases, they go along the path of complicating the criteria; in others, they try to simplify them. The potential of domestic classifications of regions as an instrument of regional policy is not fully used, which requires concrete steps from scientists and practitioners, in particular, adjusting existing classifications over time, tracking the movement of regions from one group to another, and developing support measures for each group of regions.